ChemInform Abstract: 3, 3′‐Diiodo‐BINOL‐Fused Maleimides as Chiral Hypervalent Iodine(III) Organocatalysts. Issue 22 (3rd June 2014) - Brenet, Simon; Berthiol, Florian; Einhorn, Jacques
Abstract An intermolecular asymmetric MCPBA promoted oxidation of aryl alkyl ketones at the α‐position by using the title catalyst is developed.